Fabrication of glass-ceramics composite by infiltration of lithium tetraborate glass into porous magnesium aluminate spinel ceramic - Kulrat N. (2023)
Magnesium aluminate spinel (MAS) glass-ceramics composite has excellent mechanical and optical properties. It can be obtained from porous ceramic by infiltrating the proper choice of glass. In this study, porous MAS ceramic was prepared by conventional sintering from MAS powder to reach a bulk density of 2.48 g∙cm-3 (70.1% of relative density). The porous MAS ceramic was then infiltrated with molten lithium tetraborate glass (Li2B4O7; LTB) at 950°C for 30 (IF30) and 60 (IF60) min. They were left to cool down to 700°C inside the furnace before being taken out to quench in ambient. The glass-ceramics composite was obtained with 98.7% and 92.1% relative density for IF30 and IF60 cases, respectively. SEM images reveal a lower degree of porosity in the IF30 case, which achieves higher flexural strength of 119.7 MPa. X-ray diffraction and Raman spectroscopy indicate that Mg2B2O5 phase (at 2θ =35°) and B2O5 functional group (at 847 cm-1) are formed during infiltration. Consequently, their micro vickers hardness increased (3.41→5.53→6.16 GPa)